Work commitment, motivation, and job satisfaction on the quality of life of teachers - Jonathan Leal; Marlene Baniel (Universidade Estadual de Alagoas, 2024)
One of the many challenges the institution has to face is to keep the teachers stay or remain in school organizations. This mixed-method research aimed to determine the work commitment, motivation, and job satisfaction on the quality of life of teachers. The participants were one-hundred eighteen (118) teachers. Data were collected using the researcher-made and standardized questionnaires and focus group interview. The independent variables in the study were the work commitment, motivation, and job satisfaction while the dependent variable was the quality of life of teachers. The findings revealed that the level of work commitment was high. The level of work motivation was high. The level of job satisfaction was high. The level of quality of life was good. The daily leisure, physical health, psychological well-being, social relations were good while the salary was fair. There was a significant difference in the quality of life based on the work commitment, motivation, and job satisfaction of teachers. There was a positive, strong association, and significant relationship among work commitment, motivation, job satisfaction, and quality of life of teachers. The study concluded that the teachers who are more fulfilled in their work have stronger attachment to their job, colleagues, and school.